Other- and all-cause Mortality among women with breast cancer. (April 2020) - Pierre-Victor, Dudith; Pinsky, Paul F.; McCaskill-Stevens, Worta
Highlights: More women with breast cancer die of other causes than of their cancer. Women with in-situ breast cancer have better survival than age-matched controls. Other-cause survival decreases with increasing breast cancer stage. Abstract: Background: Advances in early detection and treatment of breast cancer (BrCA) have led to better survival. Consequently, more women with BrCA now die from non-BrCA causes. We investigated all-cause and other-cause (non-BrCA) survival among women with BrCA. Methods: From the Prostate, Lung, Colorectal and Ovarian (PCLO) cohort, we selected women diagnosed with BrCA from 1994-2014. To compare survival of cases to non-cases, we used exposure density sampling. We computed standard mortality ratios (SMRs) and performed Cox proportional hazards models with matched case-control sets, controlling for demographics (Model I) and additional covariates (Model II). We also examined survival by stage within BrCA cases. Results: Among 78, 215 women enrolled in PLCO, there were 1211 in-situ and 4790 invasive BrCA cases. 15-year survival rates were 97.1 % (BrCA-specific) and 77.2 % (other-cause) among in-situ and 86.4 % (BrCA-specific) and 73.4 % (other-cause) among invasive cases. For other-cause mortality, in-situ cases had lower risk in models I (HR = 0.74; 95 % CI:0.62-0.89) and II (HR = 0.75; 95 % CI:0.62-0.92) versus controls. All-cause mortality HRs for in-situ cases were 0.83 (95 % CI:0.70-0.99) and 0.85 (95 % CI:0.70–1.02) in Models I and II, respectively. Other-cause mortality was similar among invasive cases and controls. Within BrCA cases, higher stage was associated with increased other-cause mortality; HRs were 1.2 (95 % CI:1.1–1.5) and 1.7 (95 % CI:1.2–2.3) for stage II and III/IV versus stage I (Model II). Discussion: Mortality from other causes exceeded that of BrCA in both in-situ and invasive cases, highlighting the importance of managing patients' chronic conditions during and following cancer treatment.